The Influence of Financial Ratios and Company Size on Stock Prices in Oil and Gas Refinery Mining Subsector Companies - Nawarni, Sanggita Indah (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2025)
This study aims to examine the influence of financial ratios and firm size on stock prices of companies in the oil and gas refinery mining subsector listed on the IDX for the period 2018-2023. In this study, stock prices are used as the dependent variable, with 5 types of independent variables: Current Ratio, Debt to Equity Ratio, Return on Asset, Earnings Per Share, and firm size. The method used is the multiple linear regression analysis model. Hypothesis testing using the model feasibility test (F-test) is deemed suitable for measuring the independent variables, namely current ratio, debt to equity ratio, debt to asset ratio, return on equity, earnings per share, and firm size against the dependent variable, which is the stock price of companies in the oil and gas refinery mining subsector. The data was processed using SPSS Statistics 25. From the results, it can be concluded that the current ratio, debt to equity ratio, debt to asset ratio, return on equity, earnings per share, and firm size do not simultaneously affect the stock price. Partially, the current ratio has a negative and significant effect on stock prices, while the debt to equity ratio, debt to asset ratio, return on equity, earnings per share, and firm size have a negative and insignificant effect on stock prices. Future researchers are expected to consider other variables and use different sectors as well to update the year of their research.